Determinants of maternal near miss events among women admitted to tertiary hospitals in Mogadishu, Somalia: a facility-based case-control study - Hassan Abdullahi Dahie (BMC, 2022)
Abstract Background A maternal near-miss is a situation in which a woman was on the verge of death but survived a life-threatening obstetric complication that happened during pregnancy, childbirth, or within 42 days after the pregnancy's termination. Survivors of near-miss events share several features with mothers who have died and identifying determinants of maternal near miss will aid in improving the capacity of the health system to reduce severe maternal morbidity and mortality. Therefore, this study was designed to identify determinants of maternal near miss incidents among women hospitalized to tertiary hospitals in Mogadishu, Somalia. Methods A facility-based unmatched case-control study was conducted in four tertiary hospitals in Mogadishu from May 1 to July 31, 2021. A total of five hundred thirty-three (178 cases and 355 controls) study participants were involved in the study. The discharge period, cases were recruited consecutively as they emerged, whereas controls were chosen using systematic sampling approach based on every fifth interval of those delivered through normal spontaneous vaginal delivery. Women who were hospitalized during pregnancy, delivery, or within 42 days of termination of pregnancy and met at least one of the maternal near-miss disease specific criteria were classified as cases, while women who were admitted and gave birth by normal vaginal delivery and resealed from the hospital without experiencing severe obstetric complications were considered controls. Participants were interviewed by well-trained research assistants using pre-tested structured questionnaire and the medical records were reviewed to identify maternal near-miss cases. Data were entered into and analyzed with SPSS 25.0. Logistic regression was used, and the significance level was set at p value ≤ 0.05. Results The most common maternal near-miss morbidities identified were severe anemia (32%), severe pre-eclampsia (19.6%), severe ante partum haemorrhage (15.0%), abortion complications (8.4%), eclampsia (6.1%), ICU admission (5.6%), severe PPH (2.8%) and severe systemic infections (2.8%). The main factors associated with maternal near-miss were rural residency [OR = 2.685, 95%CI: (1.702-4.235)], age below 20 years [OR = 2.728, 95%CI: (1.604-4.5640)], unmarried [OR = 2.18, 2.18, 95%CI (1.247-3.81)], lack of formal education [OR = 2.829, 95%CI: (1.262-6.341)], husband's unemployment [OR = 2.992, 95%CI: (1.886-4.745)], low family income [OR = 3.333, 95%CI (1.055-10.530)], first pregnancy before 18 years of age [OR = 3.091, 95% CI: (2.044-4.674)], short birth interval [OR = 5.922, 95%CI: (3.891-9.014)], previous history of obstetric complication [OR = 6.568, 95%CI: (4.286-10.066)], never attended ANC services [OR = 2.687, 95%CI: (1.802-4.006)], lack of autonomy in seeking medical help [OR = 3.538, 95%CI: (1.468-8.524)], delivery at non-health facility setting [OR = 4.672, 95%CI: (3.105-7.029)], experiencing the second delay [OR = 1.773, 95% CI: (1.212-2.595)] and stillbirth of the last pregnancy [OR = 5.543, 95%CI: (2.880-10.668)]. Conclusion and recommendation. Lack of maternal education, lack of antenatal care, lack of autonomy to seek medical assistance, short birth interval, rural residence and delay in accessing obstetric services were identified as factors associated with maternal near-miss morbidity. As a result, the study suggests that those modifiable characteristics must be improved in order to avoid severe maternal complications and consequent maternal death.